Development Guidelines for the Digital Marketing Potential of the Freshfin Community Enterprise Network in Suphan Buri Province - Katepan, Pimolwan; Srisuantang, Santi (Journal of Humanities and Social Sciences Thonburi University, 2022)
The purposes of this research were 1) to study the digital marketing potential of the Freshfin Community Enterprise Network, 2) to study the participation in the development guidelines preparation for the digital marketing potential of the Network, and 3) to synthesize the development guidelines for the digital marketing potential of the Network through a participatory process by using a qualitative research method. The results reveal that 1) the Freshfin Community Enterprise Network has a moderate level of digital marketing potential. 2) Participation in the development guidelines preparation for the digital marketing potential of the Network, found that network members participated in the overall at a high level consisted of involving in decision-making, participated in implementation, participated in the preparation of the development plan, participated in benefit sharing, and participated in assessment. 3) Development guidelines for the digital marketing potential of the Freshfin Community Enterprise Network, found that governments and relevant agencies should provide support in following areas: (1) production or planning; (2) marketing management or product/service management; (3) funding, and (4) knowledge and information management.